Global reporting initiative's environmental reporting: A study of oil and gas companies - Alazzani, Abdulsamad; Wan Hussin, Wan Nordin (Elsevier, 2013)
In this paper, we ask if the use of a voluntary standard assessment system for environmental reporting could help mitigate the damage caused by oil and gas companies to developing nations.What level of data reporting by these companies is needed to allow the assessment of environmental practices? To answer these questions, we evaluate the environmental practices of eight oil and gas companies against the Sustainability Reporting Guidelines issued in 2006 by the Global Reporting Initiative (GRI).Content analysis of their environmental reports 2009 indicates that they made reasonable efforts to disclose their environmental performance in accordance with the GRI Sustainability Reporting Guidelines. These guidelines appear to provide a robust and readily available tool for reporting comprehensive progress concerning all aspects of environmental activities.The voluntary adoption of the guidelines by a vast majority of the oil and gas companies increases transparency, credibility and comparability in sustainability reporting.In addition, five of the eight oil and gas companies disclosed that they had obtained third-party assurance of their sustainability reports.